The Effect of Financial Knowledge, Technology, and Behavioral Control on Student Financial Behavior - Fridayani Wongsowinoto; Susanto Susanto (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
At this time, many business activities are assisted by communication technology to stay can gain profit in global competition, which is where all the information becomes fast moving. Therefore, economic development in Indonesia is getting increased. Another factor underlies this economic growth because more than 80% are students who have good financial knowledge and behavioral control and are conceptualized after marketing strategies in marketing management. This study aims to determine The Effect of Financial Knowledge, Technology, and Behavioral Control on Student Financial Behavior and the factors that underlie student behavior increasing in the use of technology in marketing. the researcher used descriptive qualitative method in analyzing this phenomenon. a phenomenon that occurs in the environment of students in utilizing technology related to financial and behavioral knowledge in improving marketing. The results of this research are Proven from 2012 to 2019, the peak was that 80% of students had been able to run a business as a form of good financial behavior to improve a good quality of life. Good financial control behavior is based on several factors such as consumption where students choose to consume goods or services according to their needs. Students can also manage personal and group cash flows well with good financial knowledge based on research and education training at colleges or schools. Students who have good financial knowledge by utilizing technology can choose to invest or save their money so that it can be used in the future. Finally, students are students who grew up in a good social environment, an environment of social behavior with good financial behavior, they will automatically form a good financial control behavior as well.